2010
DOI: 10.1128/jvi.00509-10
|View full text |Cite
|
Sign up to set email alerts
|

Three Arginine Residues within the RGG Box Are Crucial for ICP27 Binding to Herpes Simplex Virus 1 GC-Rich Sequences and for Efficient Viral RNA Export

Abstract: ICP27 is a multifunctional protein that is required for herpes simplex virus 1 mRNA export. ICP27 interacts with the mRNA export receptor TAP/NXF1 and binds RNA through an RGG box motif. Unlike other RGG box proteins, ICP27 does not bind G-quartet structures but instead binds GC-rich sequences that are flexible in structure. To determine the contribution of arginines within the RGG box, we performed in vitro binding assays with N-terminal proteins encoding amino acids 1 to 160 of wild-type ICP27 or arginine-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Therefore, defects in viral replication seen in RGG box substitution mutants can be attributed to effects of hypomethylation on export (30) and regulation of functional interactions with cellular proteins (31). Hypomethylation of ICP27 does not affect its ability to bind RNA (8), and, as we showed here, there is no demonstrable effect on ICP27 import. This work was supported by National Institute of Allergy and Infectious Diseases (NIAID) grants AI61397 and AI21215.…”
mentioning
confidence: 46%
See 1 more Smart Citation
“…Therefore, defects in viral replication seen in RGG box substitution mutants can be attributed to effects of hypomethylation on export (30) and regulation of functional interactions with cellular proteins (31). Hypomethylation of ICP27 does not affect its ability to bind RNA (8), and, as we showed here, there is no demonstrable effect on ICP27 import. This work was supported by National Institute of Allergy and Infectious Diseases (NIAID) grants AI61397 and AI21215.…”
mentioning
confidence: 46%
“…Furthermore, the interaction of ICP27 with two cellular proteins, SRPK1, an SR-splicing protein-specific kinase, and Aly/ REF, an RNA export adaptor protein, was diminished under conditions of hypomethylation that resulted from infection with the substitution mutants or from adding the methylation inhibitor adenosine dialdehyde (AdOx) to HSV-1 KOS-infected cells (31). Although arginine methylation has been shown to affect the RNA and DNA binding activities of several proteins (4,14), we recently reported that hypomethylation of ICP27 does not affect its ability to bind GC-rich sequences in vitro; neither does it appear to affect RNA export during HSV-1 infection (8). However, we found that arginine methylation does regulate ICP27 export to the cytoplasm.…”
mentioning
confidence: 99%
“…Secondary structure predictions indicate that the N-terminal region up to ϳ240 residues is disordered. Circular dichroism (CD) analysis and nuclear magnetic resonance (NMR) studies on the N-terminal half (residues 1 to 160) of the protein have in fact confirmed that this region is predominantly randomcoils with no rigid three-dimensional structure (22). Another NMR study revealed that a short stretch of ICP27 (residues 103 to 110) was sufficient for binding to the RNA recognition motif of Aly/REF and was linear in the structure (23).…”
mentioning
confidence: 84%
“…Recent crystal structure studies demonstrated that the structure of ICP27 does not have KH domains and that its C-terminal region does not fold into a potentially RNA-binding hnRNPK-like structure (4, 5). ICP27's RGG motif has been shown to directly bind RNA (37,38) and appears to play a significant role in alternative polyadenylation and a lesser role in splicing inhibition. However, our in vitro transfection experiments and previous reports (18,20) showing that the RGG motif is not required for ICP27-mediated splicing inhibition suggest that there may be other RNA binding sites in ICP27 or that unknown adaptor proteins are involved in recognizing the C-rich sequences near the 5′ splice site.…”
Section: Splicing Inhibition Mediated By Icp27 and Cytosine-rich Sequmentioning
confidence: 99%